Role of biological medicines in chronic rhinosinusitis with nasal polyps - Systematic review and meta-analysis - Vila-Real-Fernandes, João (2023)
Introduction: Chronic rhinosinusitis with nasal polyps is an inflammatory disease associated with high morbidity and quality of life impairment. The aim of this article is to evaluate the efficacy of new monoclonal therapies in the control of disease refractory to the available therapies and to discuss the multiple factors that should be taken into consideration in the use of these types of drugs. Methods: Systematic review with meta-analysis on the efficacy of biological therapies in chronic rhinosinusitis with nasal polyps. It was also assessed, through a review of the relevant literature, the cost-benefit of biologic treatments. Results: In total, the meta-analysis included 11 randomized clinical trials that evaluated 4 monoclonal antibodies and all antibodies showed improvement in quality of life and a positive impact on the extent of the disease, despite its huge economical burden. Conclusion: In this systematic review, we were able to verify that dupilumab was the monoclonal antibody with the greatest impact, both on quality of life and on the extent of the disease. However, further studies are needed in the future to better assess the long-term effect of these new therapies. Furthermore, given the economic impact of its use, it is imperative to efficiently assess which patients benefit the most from biologic therapies.